2009
DOI: 10.1007/s10549-009-0619-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of ALDH1 in breast cancer: a story of stem cells and tumor microenvironment

Abstract: The concept of cancer cells being hierarchically organized and arising from their own progenitor stem cells will have important implications on cancer therapy. If this hypothesis were to be true then the paucity of estrogen receptors in stem cells as well as their inherent drug resistance mechanisms pose a challenge to current targeted therapies. In this study, we sought to examine the prognostic relevance of ALDH1, a putative cancer stem cell marker, by immunohistochemistry. The four cohorts analyzed included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
135
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 36 publications
21
135
4
4
Order By: Relevance
“…Nine out of 32 studies, with heterogeneous study design, met the predefined inclusion criteria and all were reviewed Of these, six studies were phase I (Dwyer et al, 2007;Woodward et al, 2007;Vlashi et al, 2009;Grisendi et al, 2010;Dwyer et al, 2011;Milane et al, 2011)and three were phase II clinical trials (Table 1) (Ueno et al, 2009;Resetkova et al, 2010;Viens et al, 2010). There was no published paper regarding phase III clinical trial on stem cell targeted therapy of breast cancer within the period of this study.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine out of 32 studies, with heterogeneous study design, met the predefined inclusion criteria and all were reviewed Of these, six studies were phase I (Dwyer et al, 2007;Woodward et al, 2007;Vlashi et al, 2009;Grisendi et al, 2010;Dwyer et al, 2011;Milane et al, 2011)and three were phase II clinical trials (Table 1) (Ueno et al, 2009;Resetkova et al, 2010;Viens et al, 2010). There was no published paper regarding phase III clinical trial on stem cell targeted therapy of breast cancer within the period of this study.…”
Section: Search Resultsmentioning
confidence: 99%
“…Another study conducted by Resetkova et al to investigate the relevance of ALDH1 as a putative cancer stem cell marker in breast cancer, did not demonstrate any correlation between ALDH1 expression with response to neoadjuvant therapy or overall survival after chemotherapy, in breast cancer patients (Resetkova et al, 2010).The clinical trials (phase I and II) in which CSCs were targeted with different mechanisms, have been summarized in Table 3.…”
Section: Targeting Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…CSC positive breast cancers, particularly ALDH1 positive cancers have been showed that to be more likely negative for ER and PR, but positive for HER2 and Ki67 correlating with more aggressive breast cancer subtypes (Morimoto et al, 2009;Zhou et al, 2010). Expression of ALDH1 was seen in stromal cells as well as epithelial cells of breast tumours which is associated with good outcome, concluding that tumour environment play a crucial role in determining the prognostic impact of stem cells Resetkova et al, 2010). Furthermore, it has been showed that knockdown of BRCA1 in primary breast epithelial cells leads to accumulation of cells expressing ALDH1 (Liu et al, 2008) In the present study, we evaluated both epithelial and stromal expression of ALDH1 to examine its relation with the clinicopathological characteristics of tumours in unselected series of breast carcinomas using immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%